Job Satisfaction and its Related Factors in Health Care Providers and Health Workers in Esfarayen, Iran - Ahmad Sadeghi; Hasan Jafari; Hossein Rouhani; Akram Zhianifard; Maryam Siavashi (Shahid Sadoughi University of Medical Sciences, 2019)
Background: Job Satisfaction in Health care organizations is one of the important pillars of health promotion, due to the role they play in the prevention, care and treatment. The aim of this study was to determine the job satisfaction and its related factors in health workers in Esfarayen. Methods: This descriptive-analytical study was carried out on 140 health care workers in Esfarayen in 2018. Data was collected using Herzberg job satisfaction questionnaire, and data were analyzed using ANOVA and t-test in SPSS21 software. Results: The mean age of participant was 37 ± 8.34. Most of them were female (70%) and married (85.5%). The average of job satisfaction was 61.45 ± 7.65 (out of 100). The highest job satisfaction score was work ability (73.54 ± 1.08) and the lowest score belonged to supervision (49.15 ± 5.73). Among the demographic variables, Job satisfaction was significantly associated with Employment Status (P<0.05.) Conclusion: Despite employees have job satisfaction, factors that increase job satisfaction of employees should be considered by the relevant authorities. Establishing suitable job standards, fair and reasonable salary, and the creation of facilities in the workplace can lead to improved employee satisfaction and, consequently, improved service quality.